2022
DOI: 10.3389/fphar.2022.949001
|View full text |Cite
|
Sign up to set email alerts
|

Nanodrugs Manipulating Endoplasmic Reticulum Stress for Highly Effective Antitumor Therapy

Abstract: Cancer is one of the leading causes of death worldwide due to high morbidity and mortality. Many attempts and efforts have been devoted to fighting cancer. Owing to the significant role of the endoplasmic reticulum (ER) in cell function, inducing ER stress can be promising for cancer treatment. However, the sustained activation of cytoprotective unfolded protein response (UPR) presents a tremendous obstacle for drugs in inducing unsolved ER stress in tumor cells, especially small-molecule drugs with poor bioav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…Intracellular ROS, which disrupt ER function, induce ER stress based on the accumulation of unfolded and misfolded proteins in the ER. Unfolded and misfolded proteins in the ER lead to the release of Bip and activation of ER transmembrane protein (IRE1α, PERK and ATF6) (Xiang et al, 2022). The phosphorylated IRE1α will covert e unspliced XBP1 protein (uXBP1) to the highly active sXBP1.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular ROS, which disrupt ER function, induce ER stress based on the accumulation of unfolded and misfolded proteins in the ER. Unfolded and misfolded proteins in the ER lead to the release of Bip and activation of ER transmembrane protein (IRE1α, PERK and ATF6) (Xiang et al, 2022). The phosphorylated IRE1α will covert e unspliced XBP1 protein (uXBP1) to the highly active sXBP1.…”
Section: Discussionmentioning
confidence: 99%
“…Endoplasmic reticulum (ER) is a vital organelle responsible for protein folding, intracellular homeostasis regulation, and cell proliferation in eukaryotic cells, which establishes ER as a potentially effective target for anticancer therapy. [ 1 , 2 , 3 ] In a previous study, we synthesized a library of doxorubicin (DOX) derivatives with various targeting subunits, including small molecules and short peptides, redirecting the intracellular fate of DOX from nucleus to ER. Our study found that the ER‐targeting efficiency of DOX positively correlated with the capability to induce immunogenic cell death (ICD).…”
Section: Introductionmentioning
confidence: 99%